(untitled) (Linguostylistic Studies, 2021)
The article examines the nominations of meteorological phenomena dangerous to humans on the basis of Eastern-steppe dialects, in particular, the nominations of rain with snow, prolonged rainfall, thick fog with light rainfall, showers, blizzards, snowfall, ice, severe frost, whirlwind, cold wind and freezing temperatures, storms, heat, droughts, etc. The comments of local residents contributed greatly to revealing the dialect peculiarities of the meteorological nominations use. Among them there are synonymous names (dryïïzhak, zaïïmerzly, zaduïïbily, zakïïlakly, proïïmerzlo do kisïïtok; svysïïtyt, reyïïve, huïïde, ïïvyie (zavyïïvaie) ïviter; ïïsype, ïïvale, meyïïte (zamyïïta) and others, comparisons (taïkyĭ ïïviter / sho do kisïïtok promeyrïïzaie, tuïïman taïkyĭ / sho yak stiïïna stoïïiit, doshch yak z vidïïra etc.), and the phraseological units (ch’ort ïïzhenits’:a, etc.) The comments of local residents testify to the nomination peculiarities of some meteorological phenomena and related concepts and processes. Fixed names are most often represented by one-word, less often – multi-word phrases (mostly attributive – lodaïïnyĭ ïïviter, ïïtykhyĭ snih, ïsylnyĭ moïïroz, laïïpatyĭ snih, etc., less often – proïïmerzlo do kisïïtok, etc.). The analysis of the use frequency of the studied demonstrators proves that the vast majority of them are commonly-used words and some nouns have variants in other speech continua. Some nominations are known in the modern Ukrainian literary language, having the identical semantics (ïvikhola, snihoïpadt, ozheyïledytsa, ïviter, ïbura, ïvykhor, sïpeka, etc.). They are also used in other dialects where they have phonetic (metélytsa, zaméta, vikhόr, etc.), word-forming (súpaty(sy), holoshchák, kotútysy, etc.), and semantic (lapátyi, vúkhor, zásukha, etc.) variants.